Introducing the Apocrypha : message, context, and significance - DeSilva, David Arthur (Grand Rapids, Mich. : Baker Academic, 2002)
The status of the apocryphal (or deuterocanonical) books has been one of the longstanding areas of disagreement among various Christian traditions. David deSilva suggests, however, that whether one views these books as Scripture (Catholic and Eastern Orthodox Christians) or not (Protestant Christians), these books should be read and studied for their inherent value. The books of the Apocrypha are a witness to faith, specifically the faith of Jewish people living from 200 B.C.E. to 100 C.E. Contemporary Christian readers find these books to be surprisingly relevant. In addition, they provide essential historical background for understanding the Judaism of Jesus' day and the Jewish matrix of early Christianity.
1. Introduction: The Value of the Apocrypha 15 -- 2. Historical Context: "The Yoke of the Gentiles" 42 -- 3. Tobit: "Better Is Almsgiving with Justice" 63 -- 4. Judith: "Hear Me Also, a Widow"
Includes bibliographical references (pages 381-395) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible - A.T - Livres deuterocanoniques - Critique, interpretation, etc